2009
DOI: 10.1111/j.1467-9922.2009.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring L2 Lexical Growth Using Hypernymic Relationships

Abstract: This study investigated second language (L2) lexical development in the spontaneous speech of six adult, L2 English learners in a 1-year longitudinal study. One important aspect of lexical development is lexical organization and depth of knowledge. Hypernymic relations, the hierarchical relationships among related words that vary in relation to their semantic specificity (e.g., Golden Retriever vs. dog vs. animal), are an important indicator of both lexical organization and depth of knowledge. Thus, this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(111 citation statements)
references
References 56 publications
(76 reference statements)
5
105
1
Order By: Relevance
“…Various studies have shown MTLD to be at least as effective as the industry standard vocd-D index, and even one of the most informative and distinguishing variables in the entire arsenal of several hundred Coh-Metrix indices (see Crossley, Salsbury, & McNamara, 2009;McNamara et al, 2010). Such successes do not mean that all the settings of the MTLD approach are optimal.…”
Section: Preliminary Analysesmentioning
confidence: 98%
“…Various studies have shown MTLD to be at least as effective as the industry standard vocd-D index, and even one of the most informative and distinguishing variables in the entire arsenal of several hundred Coh-Metrix indices (see Crossley, Salsbury, & McNamara, 2009;McNamara et al, 2010). Such successes do not mean that all the settings of the MTLD approach are optimal.…”
Section: Preliminary Analysesmentioning
confidence: 98%
“…These associations tap into different domains of lexical knowledge, such as variation Koizumi & In'nami, 2012), appropriateness (Iwashita et al, 2008), fluency (Iwashita et al, 2008;Lu, 2012), sophistication (Lu. 2012), abstractness and sense relations (Crossley et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…L2 learners tend to produce less specific words as their L2 experience increases (Crossley et al, 2009), which contributes to raters' judgment of overall lexical proficiency . More proficient L2 learners likely rely on strategies by using more general/holistic terms to compensate for specific words which they may not know or have difficulty accessing (e.g., water vs. pond) (Faerch & Kasper, 1984).…”
Section: Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, the absence of significant correlation between percentage scores and oral ability in the study indicates potential problems with the frequency-based principle for assessing vocabulary knowledge (Nation & Webb, 2011). Therefore, in order to further investigate the relationship between vocabulary knowledge and L2 speaking ability, it is important to be aware of other aspects of vocabulary knowledge besides frequency such as L1 cognate (Bardel, Gudmundson, & Lindqvist, 2012), speed of lexical retrieval (Fitzpatrick & Izura, 2011;Miralpeix & Meara, 2014), abstractness (Crossley, Salsbury, & McNamara, 2009), sense relations (Crossley, Salsbury, & McNamara, 2010), richness and sophistication (Lu, 2012), and multi-word units (Kyle & Crossley, 2014).…”
Section: Productive Vocabulary Measurementioning
confidence: 99%